2003
DOI: 10.1074/jbc.m301991200/6493
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Intersubunit Interactions between S4 and S5 Transmembrane Segments of the Shaker Potassium Channel

Abstract: Voltage-gated potassium channels are transmembrane proteins made up of four subunits, each comprising six transmembrane (S1-S6) segments. S1-S4 form the voltage-sensing domain and S5-S6 the pore domain with its central pore. The sensor domain detects membrane depolarization and transmits the signal to the activation gates situated in the pore domain, thereby leading to channel opening. An understanding of the mechanism by which the sensor communicates the signal to the pore requires knowledge of the structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 4 publications
2
22
3
Order By: Relevance
“…The S1–S4 bundles form the VSDs and are organized in a manner that agree with previous experimental results (Broomand et al, 2003; Neale, 2003): the VSD of one subunit sits next to the pore domain of the adjacent subunit and the connection between the VSD and the pore of the same subunit is insured by an S4–S5 helical linker (Figure 1). The VSD, of which all the segments are oriented roughly perpendicular to the membrane plane, shows rather tight packing.…”
Section: Molecular Insight Into the Function Of Kv Channelssupporting
confidence: 87%
“…The S1–S4 bundles form the VSDs and are organized in a manner that agree with previous experimental results (Broomand et al, 2003; Neale, 2003): the VSD of one subunit sits next to the pore domain of the adjacent subunit and the connection between the VSD and the pore of the same subunit is insured by an S4–S5 helical linker (Figure 1). The VSD, of which all the segments are oriented roughly perpendicular to the membrane plane, shows rather tight packing.…”
Section: Molecular Insight Into the Function Of Kv Channelssupporting
confidence: 87%
“…Thus the origin of the difference in the e o values between Shaker and hERG remains to be established. Structural differences in other parts of the voltage sensor, including the additional negative charges, or configuration of water crevices surrounding the cytoplasmic end of the sensor [16,28] might contribute to the differences in e o values between hERG and Shaker. One intriguing possibility is that the aqueous crevice at the intracellular phase of S4 could be smaller in hERG compared with other Kv channels, as this would increase the size of the electric field across which S4 charges need to move, and thereby reduce the net gating charge translocated.…”
Section: Discussionmentioning
confidence: 97%
“…The state-dependent changes in the S4-S5 arrangement seen here for HCN1 channels show intriguing similarities and differences with Shaker Kv channels (8, 18, 25, 36). Thus, certain pairs of Shaker residues near the extracellular ends of S4 and S5 form intersubunit disulfide bonds and Cd 2+ coordination sites (8, 25, 36).…”
Section: Discussionmentioning
confidence: 59%
“…Thus, certain pairs of Shaker residues near the extracellular ends of S4 and S5 form intersubunit disulfide bonds and Cd 2+ coordination sites (8, 25, 36). In contrast, Elliott et al (18) found that a different pair of Shaker residues near the external ends of S4 and S5 form an intrasubunit Cd 2+ coordination site preferentially when the channels are activated by depolarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation